Implementation of E-Health Based Technology to Improve the Health Status of the Elderly: A Literature Review - Filipus Y. Boibalan; Sukihananto (Lentera Perawat, 2024)
The number of elderly from year to year continues to increase, this has a significant impact on health services. The significant addition of the elderly and the worsening of the situation including decreased health, altered emotional status, inability to do activities independently make some people consider the elderly a burden. Objective: Providing ideas and ideas from the results of literature review on the implementation of E-health-based technology to improve the health status of the elderly, using smartphones to measure elderly activities, security and safety of the elderly. The method used in this research is literature review with keywords namely "technology", "elderly", and "degree of health". Searching for academic journals through Online Databases including: Science Direct, Google Scholar, ProQuest and clinical key from 2015-2022. The results of the review of 10 journals that discuss the technology of monitoring the elderly remotely via smartphones can be concluded if the development of technology to monitor the development of the elderly remotely is very satisfying because it can help caregivers and health workers in monitoring activities, the state of the elderly, and minimizing adverse events. It is hoped that future researchers can examine the ability of users to apply technology and user preparedness and costs in using this technology.